Study of Histamine Detection using Liquid Chromatography and Gas Chromatography - Muhammad Abdurrahman, Munir; Muhammad Mukram, Mohamed Mackeen; Lee, Yook Heng; Khairiah Haji, Badri (The Academy of Sciences Malaysia, 2021)
Histamine is a heterocyclic amine shaped by decarboxylation of the histidine. It is a compound that lack chromophore and involatile. However, the detection of histamine is imperative due to the characteristic of histamine has given several disadvantages in food industry. This paper describes methods for histamine detection by employing high performance liquid chromatography and gas chromatography. The derivatization techniques required for both methods in order to increase the sensitivity of chromatography analysis. Two derivatizing agents were applied in this study such as 9-flourenilmethyl chloroformate (FMOC – Cl) for HPLC analysis whereas for GC analysis a N,O-bis (trimethylsilyl)acetamide (BSA) was used. Method validation was in accordance to Commission Decision 657/2002/CE. The validation of specificity, linearity, precision, accuracy, detection limit and quantitation limit results indicate that the methods were acceptable. The linear range for both methods were at 0.16 – 5.00 µg∙mL-1 . The determination of histamine using GC showed the superiority of this instrument compared to HPLC. Method applicability was also checked on real sample namely mackerel in order to acquire a satisfactory recovery for both methods.